Burden of Enteropathogens Associated Diarrheal Diseases in Children Hospital, Nepal - Sherchand, Jeevan B; Yokoo, Michiyo; Sherchand, Ojaswee; Pant, Arun R; Nakogomi, Osamu (Scientific World, 2010)
Diarrheal disease caused by bacteria, parasites or viruses continues to be an important cause of morbidity and mortality among young children in developing countries. Methods currently used in public health laboratories do not allow for the identification of rotavirus, Cyclospora and pathogenic E.coli infection though they represent as an etiology in large proportion of patients with diarrhea, the possibility exists that a portion of the undiagnosed illness may be attributable to one or more of the above enteropathogens. In a view to determine the causative agents of diarrhoea, the current study described the various enteropathogens associated with diarrhoea in hospitalized children. Stool samples were collected from children under 11 years of age who developed diarrhoea and were admitted to Kanti Children's Hospital between May to October 2007 and investigated in Tribhuvan University, Institute of Medicine, Health Research Laboratory; by using both the combination of microbiological and immunological tools ( EIA for rotavirus detection, standard parasitological procedure for Cyclospora and other intestinal parasites, and selective culture method and serotyping were used to differentiate the species of bacteria). A total of 440 diarrhoeal stool samples were collected and 285 (64.8%) enteropathogens were identified. The highest infection was due to intestinal parasites 104/285 (36.5%) followed by rotavirus 92/285 (32.3%); pathogenic bacteria 57/285 (20%) and Cyclospora 32/285 (11.2%). Among the pathogenic bacteria (20%) isolated, the predominant bacteria were Shigella species (36.8%); Vibrio species (26.3%); Escherichia coli (22.8%) and Salmonella species (14.03%) respectively. Various enteropthogens responsible for diarrhoea especially rotavirus, different pathogenic bacteria and Cyclospora infection, which are not examined routinely in public health laboratories, were found in significant proportion as a cause of diarrhoeal illness in children. The infection was peak in children under 2 years of age and was highest in rainy season. Key words: Burden; Diarrhea; Enteropathogens; Children; Nepal. DOI: 10.3126/sw.v7i7.3830 Scientific World Vol.7(7) 2009 pp.71-75